1993
DOI: 10.2175/wer.65.6.7
|View full text |Cite
|
Sign up to set email alerts
|

Process and kinetic analysis of nitrification in coupled trickling filter/activated sludge processes

Abstract: zyxwvutsrqponmlkjihgfedcbaZYXWVUTSRQPONMLKJIHGFEDCBA A model for nitrification in a coupled trickling filter/ activated sludge system is presented. Nitrification will occur in the trickling filter component of the system when the organic loading to the trickling filter is about 1 kg BOD 5 /m 3 .d(60 lb BOD 5 /1 000 ft 3 -day) the degree of nitrification will increase as the organic loading decreases below this value. Nitrification in the upstream trickling filter has two impacts on the downstream suspended gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…The process was first modeled by use of a complex activated sludge model (IWA Activated Sludge Model No. 1), with estimates of nitrifier seed organisms (Parker and Richards,1994) and then by simpler kinetic models incorporating seeding (Daigger et al, 1993). Both modeling approaches were later confirmed against full-scale plant data (Bratby et al, 1999, Biesterfeld et al, 2003.…”
Section: Tf/pas Processmentioning
confidence: 95%
See 1 more Smart Citation
“…The process was first modeled by use of a complex activated sludge model (IWA Activated Sludge Model No. 1), with estimates of nitrifier seed organisms (Parker and Richards,1994) and then by simpler kinetic models incorporating seeding (Daigger et al, 1993). Both modeling approaches were later confirmed against full-scale plant data (Bratby et al, 1999, Biesterfeld et al, 2003.…”
Section: Tf/pas Processmentioning
confidence: 95%
“…Demonstration of effectiveness at full scale is also more satisfactory than at either pilot or bench scale. Richards, 1984;Daigger et al, 1993;Bratby et al, 1999;Biesterfeld et al, 2003 Chemostat • Lack of consistent response in mainstream reactor when seeded from chemostat Short SRT • Increased nitrifier activity in bench scale experiments • Nitrification in pilot high purity oxygen activated process at pilot-scale • Lam and Babcok, 1998, Plaza et al,2001, Zimmerman et al, 2004• Riska et al, 2004 Parallel Seed…”
Section: Figure 6 -Comparison Of Effectiveness Of Two Bioaugmentationmentioning
confidence: 99%
“…Bailey et al (2008) patented a process that is similar to the parallel-plants approach, except that it uses nitrifying secondstage ASP to bioaugment the first stage. Daigger et al (1993) improved nitrification of an ASP by bioaugmenting waste biomass from a nitrifying trickling filter.…”
Section: Bioaugmentation Strategiesmentioning
confidence: 99%
“…Kos [6] has reported that the apparent SRT of a nitrifying wastewater treatment system can be decreased from a range of 13 to 18 d, down to between 7 and 10 d, by nitrifying NH 3 from the centrate from a sidestream and then recycling the excess biomass into the main bioreactors. Rittmann et al [7] has stated that the apparent SRT can be decreased from 15 to 1.5 d to achieve effluent with NH þ 4 -N concentrations less than 1 mg/L, when at least 15 mg/L of active nitrifying biomass was added into the influent stream of a chemostate that was treated with 33 mg NH þ 4 -N/L d. Daigger et al [8] found that nitrification occurred in an aerobic bioreactor tank as a result of sloughing of nitrifying biomass from an upstream trickling filter. Abeysinghe et al [4] compared the effects of bioaugmentation with 5 d SRT in 4˚C to 2 d SRT in 22˚C in a laboratory, with the application of a bioaugmentation product (INOC 8166) containing highly enriched ammonia-oxidizing bacteria.…”
Section: Introductionmentioning
confidence: 99%